Gastric carcinoma leading to metastatic spinal cord compression - Daterdiwala, Nida Fatima; Memon, Hina Fatima; Erum, Asra; Asif Husain Osmani (Journal of the Pakistan Medical Association, 2024)
Gastric cancer is described as a malignancy occurring in the region between the gastroesophageal junction and the pylorus. According to the histology, majority of gastric cancers are classified as adenocarcinomas. The prevalence of bone metastasis in the general population is 2-3%. Here, an unusual case of a 73-year-old male is discussed who presented on September 10, 2023, with symptoms of lower back pain and bowel and urinary incontinence. His MRI results showed mild indentation along with nerve impingement and hypertrophied ligamentum flavum at the level of L5/S1. Within D11 and D12 vertebral bodies, diffuse abnormal signals were appreciated predominantly along posterior corners. CT scan of the abdomen showed sessile hypodense area along the mucosa of the posterior wall of the gastric antrum. Histopathology further confirmed the diagnosis with the appearance of signet ring cells. He was managed with supportive care and palliative radiotherapy. The patient expired on the 28th day of being discharged. Keywords: Stomach Neoplasm, Metastasis, Spinal Cord Compressions, Tumour.